Pengaruh Likuiditas, Pertumbuhan Penjualan, dan Risiko Bisnis Terhadap Nilai Perusahaan - Dewi, Ida Ayu Puspita Trisna; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p04, 2019)
This study aims to analyze the effect of Liquidity, Sales Growth, and Business Risk to Company Value (study on Telecommunication Company listed on Indonesia Stock Exchange period 2011-2016). The study population includes all telecommunication companies listed on Indonesia Stock Exchange period 2011-2016. The research population data are 30 companies with observation samples of 5 companies. The method used in this research is purposive sampling method. Data analysis was tested by using multiple linear regression analysis. The results of this study indicate that liquidity has a positive effect on corporate value, sales growth positively affect the value of the company and business risk negatively affect the value of the company. Keywords: liquidity, sales growth, business risk and corporate value